The emerging role of neutrophil extracellular traps in cancer: from lab to ward - Zhong, Wentao; Wang, Qianyu; Shen, Xiaofei; Du, Junfeng (Frontiers in Oncology, 2023)
Neutrophil extracellular traps (NETs) are web-like structures derived from neutrophils, which typically consist of DNA, released from the nucleus or mitochondria, and decorated with histones and granule proteins. They are well known as an important structure in innate immunity to eliminate pathogenic bacteria, similar to neutrophils. Initially, NETs are reported to take part in the progression of inflammatory diseases, now, they have also been implicated in the progression of sterile inflammation such as autoimmune disease, diabetes, and cancer. In this review, we will describe the recent studies which have investigated the role of NETs in the development of cancer, especially metastasis. We also prescribe the strategies for targeting NETs in the multiple cancer types, which suggest that NETs are a promising treatment for cancer patients.